Gerontological social work and ethnic diversity: a reflection from the case of the Aymara and Mapuche communities in Chile - Gallardo Peralta, Lorena Patricia; Soto Higuera, Abel; Vargas Pizarro, Luis (Critical Proposals in Social Work, 2022)
Emphasizing cultural diversity in the aging process - an individual and social level - has become a trend and a necessity in recent years from social gerontology and from Gerontological Social Work. In this line, the objective of this presentation is the analysis of the possible differences and at the same time the similarities of the successful aging process of the two most populous native ethnic groups in Chile: mapuche and aymara, and to describe the cultural practices of indigenous older people and analyzes the relationship between successful aging and ethnic-culturalidentity. Likewise, to delve into the practical and theoretical applications of indigenous knowledge / worldview in Chilean social work. Method: Quantitative and cross-sectional study conducted between August and November 2017. Participated in this study 569 indigenous older people living in rural areas of the Arica and Parinacota and La Araucanía regions. Through a structured interview the Successful Aging Inventory (SAI), devised by Troutman et al. (2011) and Multigroup Ethnic Identity Measure (MEIM) developed by Phinney (1992) Descriptive, bivariate and correlation analyzes are performed through the IMB-SPSS program, version 25. Discussion / conclusion: The results indicate a successful aging process for both indigenous peoples, in addition a high maintenance of indigenous cultural practices is noted and, finally, a positive and significant correlation is observed between successful aging and ethnic identity. From the Social Work discipline, in Chile, the need for greater specialization in the subject of aging is evident, through new methodologies, within the framework of an ethic of convergence, which is a mediating bridge between a dialogical ethic and conflictive, thereby allowing progress towards an intercultural ethic